2019
DOI: 10.1042/bst20170410
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial glycans and their interactions with lectins in the innate immune system

Abstract: Bacterial surfaces are rich in glycoconjugates that are mainly present in their outer layers and are of great importance for their interaction with the host innate immune system. The innate immune system is the first barrier against infection and recognizes pathogens via conserved pattern recognition receptors (PRRs). Lectins expressed by innate immune cells represent an important class of PRRs characterized by their ability to recognize carbohydrates. Among lectins in innate immunity, there are three major cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…These observations are in agreement with previous results obtained using purified CPSs of S. suis serotypes 2 and 14 and of GBS serotypes III and V ( 25 ), suggesting that DCs appear to respond to CPSs in a patterned manner, seemingly independent from their different structural features. This warrants further investigations into the involvement of members from the large family of lectin receptors as possible candidates ( 49 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with previous results obtained using purified CPSs of S. suis serotypes 2 and 14 and of GBS serotypes III and V ( 25 ), suggesting that DCs appear to respond to CPSs in a patterned manner, seemingly independent from their different structural features. This warrants further investigations into the involvement of members from the large family of lectin receptors as possible candidates ( 49 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that S-layer proteins interact with host C-type lectin receptors (CLRs) (24,25). Myeloid CLRs are pattern recognition receptors (PRRs) that are crucial for innate immunity and protection from invasive pathogens by initiating innate sensing and early antimicrobial responses (26,27). Furthermore, CLRs play an important regulatory role and maintain immune homeostasis in the gut (28).…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of lectins, including vasodilation, are closely related to their connection with carbohydrates. In fact, most of these activities are mediated by interactions with glycans found in glycoconjugates on the cell surface 32,33 . Thus, in the present study possible mechanisms involved in DRL‐induced vasodilation were predicted by molecular docking simulations with some candidate glycoconjugates found on the membrane surface.…”
Section: Discussionmentioning
confidence: 85%
“…The third group of tested N ‐glycans was the hybrid type, which further to having properties of the previous types, also exhibit LacNAc and oligomannosidic branches 33 . DRL interacted quite well with the tested hybrid glycans, exhibiting scores of −55.57 and −45.41 for HYB1 and HYB2, respectively.…”
Section: Discussionmentioning
confidence: 95%